Paracrine Effects of FGF23 on the Heart - Leifheit-Nestler, Maren; Haffner, Dieter (Frontiers in Endocrinology, 2018)
Fibroblast growth factor (FGF) 23 is a phosphaturic hormone primarily secreted by osteocytes to maintain phosphate and mineral homeostasis. In patients with and without chronic kidney disease (CKD), enhanced circulating FGF23 levels associate with pathologic cardiac remodeling, i.e. left ventricular hypertrophy (LVH) and myocardial fibrosis, and increased cardiovascular mortality. Experimental studies demonstrate that FGF23 promotes hypertrophic growth of cardiac myocytes via FGF receptor 4-dependent activation of phospholipase Cγ/calcineurin/nuclear factor of activated T cell signaling independent of its co-receptor klotho. Recent studies indicate that FGF23 is also expressed in the heart, and markedly enhanced in various clinical and experimental settings of cardiac remodeling and heart failure independent of preserved or reduced renal function. On a cellular level, FGF23 is expressed in cardiac myocytes and in other non-cardiac myocytes, including cardiac fibroblasts, vascular smooth muscle and endothelial cells in coronary arteries, and in inflammatory macrophages. Current data suggests that secreted by cardiac myocytes, FGF23 can stimulate pro-fibrotic factors in myocytes to induce fibrosis-related pathways in fibroblasts and consequently cardiac fibrosis in a paracrine manner. While acting on cardiac myocytes, FGF23 directly induces pro-hypertrophic genes and promotes the progression of LVH in an autocrine and paracrine fashion. Thus, enhanced FGF23 may promote cardiac injury in various clinical settings not only by endocrine but also via paracrine/autocrine mechanisms. In this review, we discuss recent clinical and experimental data regarding molecular mechanisms of FGF23´s paracrine action on the heart with respect to pathological cardiac remodeling.